KETERKAITAN AKTIVITAS INDUSTRI DI KLASTER INDUSTRI BATIK BAYAT KABUPATEN KLATEN - Avinda Dyah N; Prihadi Nugroho (Teknik PWK (Perencanaan Wilayah Kota), 2016)
The existence of business clusters can strengthen the resilience of the economy which mainly rely on existing potential. In 2006, industry and trade sector dominated by SMEs at 99% and approximately 30% of the population of SMEs in Indonesia are in Central Java. One of Klaten district, known as the dominance of small industrial activity. The flagship product of Klaten in 2013 is one industrial clusters batik. Industrial cluster is one of the small industry that has become the main economic commodities in Bayat, Klaten. Batik has been a source employement for the majority of people in Bayat, Klaten. Batik as local economic development able to create an ascsociation with related business like entrepreneur/batik craftsmen, supplier of raw materials, and buyer. The linkage will certainly have an impact on the business dependence. The dependence of batik craftsmen on suppliers of raw materials and the buyer mat ant any time be a time bomb for enterpreneurs/craftsmen batik. Moreover, in its development obstacles in the cluster development such as marketing and promotion. The lack of an extensive marketing campaign and resulted in many employers/batik craftsmen who rely showroom and cooperative. The weakness of mutual trust between employers/batik craftsmen in the sharing information is also an obstacle in the development of clusters. Lack of government’s role related to the flow production such as capital, marketing, and information sharing is one of the constraints in the batik industry cluster development. Constraints such activity causes the linkage of economic activity, social activity, horizontal, and vertical disturbed. This is certainly going to disrupt the continuity of batik industry cluster in Klaten. Results from this research that form of activity linkages Cluster Batik Bayat can be divided into three categories, namely new batik industry, heritage batik industry, and government-owned industries. Form of horizontal and vertikal linkages occur at variable raw material procurement, information sharing, market demand, and marketing. The highest form of horizontal linkages contained in the government-owned industries and vertical linkages form the dependence of business which at times can be reduced by buyer and suppliers of raw materials.